2019
DOI: 10.1002/ece3.5268
|View full text |Cite
|
Sign up to set email alerts
|

From microsatellites to single nucleotide polymorphisms for the genetic monitoring of a critically endangered sturgeon

Abstract: The use of genetic information is crucial in conservation programs for the establishment of breeding plans and for the evaluation of restocking success. Short tandem repeats (STRs) have been the most widely used molecular markers in such programs, but next‐generation sequencing approaches have prompted the transition to genome‐wide markers such as single nucleotide polymorphisms (SNPs). Until now, most sturgeon species have been monitored using STRs. The low diversity found in the critically endangered Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…A recent rising molecular tool for parentage analysis is single nucleotide polymorphisms (SNPs), since the availability of genomic resources and multiplexed detecting methods have been greatly enhanced by NGS and bioinformatic techniques [ 13 ]. Over the last decade, SNPs have been used in parentage assignment [ 14 ], relatedness analysis [ 15 ], sibship assessment [ 3 ], population structure [ 16 ] or mating system research [ 17 ] in about 20 fish species [ 13 ]. Compared to microsatellites, SNPs are superior in their abundance over genomes [ 12 ], lower mutation rates [ 18 ], higher automation and easier standardization across laboratories [ 19 ], which effectively reduce the cost of time and genotyping errors caused by human factors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent rising molecular tool for parentage analysis is single nucleotide polymorphisms (SNPs), since the availability of genomic resources and multiplexed detecting methods have been greatly enhanced by NGS and bioinformatic techniques [ 13 ]. Over the last decade, SNPs have been used in parentage assignment [ 14 ], relatedness analysis [ 15 ], sibship assessment [ 3 ], population structure [ 16 ] or mating system research [ 17 ] in about 20 fish species [ 13 ]. Compared to microsatellites, SNPs are superior in their abundance over genomes [ 12 ], lower mutation rates [ 18 ], higher automation and easier standardization across laboratories [ 19 ], which effectively reduce the cost of time and genotyping errors caused by human factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more economical and efficient approaches using NGS have been developed, such as restriction site-associated DNA sequencing (RADSeq) [ 14 ], double digest RADSeq (ddRADSeq) [ 15 ], MIG-Seq (multiplexed ISSR genotyping by sequencing) [ 16 ], genotyping-in-thousands by sequencing (GT-Seq) [ 17 , 18 ], and genotyping by random amplicon sequencing, direct (GRAS-Di) [ 19 , 20 ]. These approaches enable simultaneous sequencing and genotyping of thousands of SNP markers, and they have been used in various species, including endangered species [ 18 , 21 ]. Although GRAS-Di has few applications thus far, GRAS-Di is useful in characterizing wildlife because it can function with the available low-quality DNA in a polymerase chain reaction (PCR)-based method and does not require a reference genome, similar to MIG-seq [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, cautious interpretation of admixture proportions inferred from microsatellites has been recommended for a number of reasons. Pitfalls associated with the use of short tandem repeats (STRs) for population genetic studies relate to their particular mechanism of mutation (Putman & Carbone, 2014), a generally assumed inferiority of neutral markers compared to functional markers (Liebl, Schrey, Andrew, Sheldon, & Griffith, 2015), possible over- (Fernández et al, 2013;Ljungqvist, Åkeson, & Hansson, 2010;Narum et al, 2008;Roques, Chancerel, Boury, Pierre, & Acolas, 2019). Moreover, we stress that in our sparrow data set, there is a considerable difference between patterns of admixture in Algeria compared to the situation in the European area of sympatry where only limited asymmetrical allelic introgression occurs (i.e., on the Iberian Peninsula: this study in accordance with Hermansen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pitfalls associated with the use of short tandem repeats (STRs) for population genetic studies relate to their particular mechanism of mutation (Putman & Carbone, ), a generally assumed inferiority of neutral markers compared to functional markers (Liebl, Schrey, Andrew, Sheldon, & Griffith, ), possible overestimate of gene flow (Balloux, Brünner, Lugon‐Moulin, Hausser, & Goudet, ; Balloux, Lugon‐Moulin, & Hausser, ), and to the fact that STRs do not represent genome‐wide variation as, for example, inferred from single nucleotide polymorphisms (SNPs) (Lemopoulus et al, ). On the other hand, several comparative studies have concluded that despite all limitations, microsatellite data are not generally less informative or less suitable for detection of patterns of divergence and admixture than genome‐wide data, for example, SNPs (Fernández et al, ; Ljungqvist, Åkeson, & Hansson, ; Narum et al, ; Roques, Chancerel, Boury, Pierre, & Acolas, ). Moreover, we stress that in our sparrow data set, there is a considerable difference between patterns of admixture in Algeria compared to the situation in the European area of sympatry where only limited asymmetrical allelic introgression occurs (i.e., on the Iberian Peninsula: this study in accordance with Hermansen et al, ).…”
Section: Discussionmentioning
confidence: 99%